<span>2/5 would be one...tell me if you need more.</span>
sqrt (5x - 9) - 1 = x
sqrt(5x - 9) = x + 1
Square both sides:_
5x - 9 = x^2 + 2x + 1
x^2 - 3x + 10 = 0
(x - 5)(x + 2) = 0
x = 5 or -2.
Lets look for for any extraneous solutions:-
x = 5 ; sqrt (5*5-9) - 1 = sqrt16 - 1 = 3 and x = 3 (right hand side of equation)
so x = 5 is a solution
x = -2: sqrt(5*-2 - 9) - 1 = sqrt (-19) - 1 and x = -2 so this is extraneous
Answer:- One solution x = 5
Well first you would find a common denominator which would be 1w and then since you multiplied 4 by 3 to get to 12 you multiply 3 by 3 which is 9. So then you would have 9/12 + 1/12 which = 10/12
Answer:
14.858
Step-by-step explanation:
16.058−1.2
=16.058−1.2
=16.058+−1.2
=14.858